Correlation between Non-Performing Assets and Performing Assets: Analyzing the Correlation and Efficiency of Non-Performing Assets in Haryana's Cooperative Banks (Journal of Advances and Scholarly Researches in Allied Education, 2018)
It is found that correlation between NPAsgross advances and performing assetsgross advances is -1. It means that there is negative correlation between NPAs and performing assets i.e. as NPAs increases performing assets decreases. The correlation coefficient indicates that there is perfect negative correlation between NPAs and performing assets. Non-Performing Assets in District Central Co-operative Banks (DCCBs) in Haryana have been evaluated after collecting data regarding from 2001-02 to 2008-09. Analysis of Gross NPAs is done by taking gross advances and total assets as base. The ratio of gross NPAs to gross advances has shown zigzag trend up to 2005-06, thereafter it has been showing an increasing trend for the DCCBs of zone-I. The banks that have highest gross NPAs ratio in 2008-09 include DCCB Ambala with 23.54, DCCB Kurukshetra with 15.95 and DCCB Yamuna Nagar with 14.32 and DCCB Panchkula with 10.93 and DCCB Karnal with 9.20. The banks that have lowest gross NPAs ratio in 2008-09 include only one DCCB i.e. DCCB Kaithal with 3.01. It means this is the only bank who manage its NPAs efficiently as compared to other banks of zone-I